Dinamisme kewangan Islam di Malaysia - Fadillah Mansor; Ab. Mumin Ab. Ghani (Siri sosioekonomi di Malaysia (University of Malaya Press), 2006)
Issues on the implementation of Islamic financial system in Malaysia; collection of articles.